ECONOMIC DIPLOMACY IN THE FUNCTION OF EXPORT PROMOTION: THE EFFECTS IN EU VERSUS NON-EU PARTNER COUNTRIES - Bugarčić, Filip; Stekić, Nenad; Tubić Ćurčić, Tijana (Political Review, 2025)
Economic diplomacy can be considered a strong driver for increasing the intensity and volume of international trade at the bilateral level. The paper aims to examine the contribution of economic diplomacy to international trade promotion by applying the gravity model. The current literature indicates an overall lack of empirical research regarding the effects of Serbian economic diplomacy. Moreover, a new approach is being introduced in the evaluation of economic diplomacy, using the sScore index as a comprehensive measure of the quality of bilateral diplomatic relations. The sample includes all countries with which Serbia actively trades, and results indicate that the quality of diplomatic relations contributes to the promotion of Serbian exports. An additional analysis was conducted on the individual effects of bilateral trade with EU and non-EU countries. General conclusions were drawn in accordance with the political and economic position of Serbia in the international framework, along with recommendations for further export promotion.